Causes and Features of Childhood Trauma in COVID-19 Period (Journal of Maternal and Child Health, 2021)
Background: In this study, we aimed to reveal the characteristics and severities of child traumas under the Covid-19 pandemic and lockdown according to trauma mechanisms, locations and age distributions, and to evaluate the results.Subjects and Method: The data of 333 pediatric trauma patients who came to our hospital during the lockdown period were analyzed retrospectively. The frequency and ratio analysis of the data obtained by the purposeful sampling method was performed. Pediatric Trauma Score, Injury Severity Score and Pediatric Glasgow Coma Scale were calculated. Gender, age distribution, trauma locations and trauma mechanisms were recorded, and distribution characteristics of the data according to trauma scores were compared. Continuous variables were analyzed using Student's t-test. Categorical variables were analyzed using the chi-square test. Statistical significance level was accepted as